Majas dan Imaji Dalam Lirik Lagu Kimi Ga Kureta Natsu Karya Reo Ieiri - Nur Hastuti; Alya Nurul Inayah (Vocational College of Diponegoro University, 2022)
Poetry is a very famous literary work. Nowadays, song lyrics are considered a part of poetry as well. Song lyrics and similar poetry elements; such as rhymes, stanzas, etc. To make the lyrics more poetic, the lyricist can use some figures of speech and images in the lyrics. This study aims to determine the figure of speech and imagery in the song